A Comprehensive Study on Adsorption Behaviour of Direct, Reactive and Acid Dyes on Crosslinked and Non-crosslinked Chitosan Beads (Journal of Fiber Bioengineering and Informatics, 2014)
Chitosan beads demonstrate good adsorption capacity in wastewater treatment. The ease with which thechitosan beads separate from the effluent and the possibilities of sorbent regeneration have made chitosanbeads a more prominent form for biosorption. However, chitosan beads form gels at pHs below 5.5, whichmakes them unsuitable to be employed in treatment process. Bifunctional agents are introduced toincrease the integrity of the beads by crosslinking chitosan. Crosslinked chitosan beads exhibit differentadsorption capacities for distinct types and categories of dyestuffs. In this study, the removal of DirectRed 80 (DR80), Reactive Yellow 25 (RY25) and Acid Blue 25 (AB25) dyes by chitosan-based beads hasbeen investigated. Variation in pH and temperature, effect of crosslinking and encapsulation of bacteriaLactobacillus casei are evaluated for their influence on the adsorption behaviour. Zeta potential andstructural characterization of the synthesized chitosan beads are performed. Adsorption equilibriumsare achieved in about five hours. The chitosan beads are crosslinked with glutaraldehyde to avoidtheir dissolution at pH 2 and the beads achieve complete removal of the three dyes within one hour.Temperature increase induces a positive effect on the adsorption of DR80, but an insignificant effecton that of RY25 and negative effect on AB25. Adsorption with the crosslinked beads at pH 5.5 and37^°C promotes the removal of RY25 and AB25 by at least two folds more than that by non-crosslinkedchitosan beads, but is found to be less effective on DR80. Significant increase of DR80 adsorption isachieved by adopting the crosslinked-bacteria-encapsulated chitosan beads while the effect on AB25 andRY25 are similar when compared to blank crosslinked beads. Langmuir and Freundlich isotherms fit theexperimental data and the pseudo-second order equation agrees very well with the kinetic data.